Effect of microwave power irradiation on TiO2 nano-structures and binder free paste screen printed dye sensitized solar cells. Issue 4 (March 2019) - Vinodhini, J.; Mayandi, J.; Atchudan, R.; Jayabal, P.; Sasirekha, V.; Pearce, J.M.
Abstract: Titanium dioxide (TiO2 ) nanostructures (nanorods and nanoparticles) were prepared using a low-cost microwave irradiation method from a polyol medium of glycerol. Titanium glycerolate and TiO2 powders were obtained in the glycerol medium for the first time with four different power densities (240 W, 480 W, 720 W, 960 W) of irradiation using a domestic microwave oven of 2.45 GHz, to understand the impact of power on morphology tuning. The structural and morphological features of the titanium glycerolate and TiO2 powders were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and Raman spectra analysis. The TiO2 was successfully used in the fabrication of photovoltaic devices and as a proof-of-concept binder free paste was prepared and successfully employed for photo-anode using screen printing on the fluorine-doped tin oxide substrate.